Retroperitoneal cystic schwannoma: A case report with review of literature - Narasimha, Aparna (Medknow Publications, 2010)
The occurrence of retroperitoneal schwannoma is uncommon and its presence may only be expressed by insidious onset of nonspecific symptoms such as vague abdominal pain. Imaging modalities like computed tomography and magnetic resonance imaging may demonstrate the tumor, but due to heterogeneity and degeneration in some tumors, it may mimic malignancy. So, fine needle aspiration cytology followed by tissue sampling through needle biopsies may be essential to confirm the diagnosis prior to the surgery. This case is reported for its rare clinical presentation, having duration of more than 40 years with cystic degenerative changes.